Cytotoxic, anti-inflammatory and adipogenic effects of selected flavonoids on cell lines - Aminuddin, Amnani; Bakhtiar, M. Taher (2014)
Naturally-occurring flavonoids have tremendous potential for producing of new therapeutic agents that provide many benefits to mankind.This study focused on the evaluation of the in vitro cytotoxic, anti-inflammatory and adipocyte differentiation effects of the selected flavonoids which were inophyllum D, calanone, and isocordataoblongic acid from Calophyllumsymingtonianum as well as morelloflavone from Garciniaprainiana on MCF 7 human breast cancer cells, RAW 264.7 macrophages and 3T3-L1 pre-adipocytes respectively. The cytotoxicity study on MCF 7 human breast cancer cells was conducted by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Meanwhile, the study of anti-inflammatory effects in RAW 264.7 macrophages and adipogenic effects on 3T3-L1 pre-adipocytes were conducted through nitrite determination assay and induction of adipocyte differentiation respectively. In the cytotoxicity study, inophyllum D was the only compounds that exhibited significant cytotoxic effect against MCF 7 human breast cancer with IC50 of 84 μg/mL. Further, all the compounds have shown anti-inflammatory effects in lipopolysaccharide (LPS)-induced RAW 264.7 macrophages with inhibition of nitrite concentration as compared to the positive control. Besides, all the compounds in the range of the tested concentrations also produced adipogenic effects on 3T3-L1 pre-adipocytes and this may suggest that they exhibited potential anti-hyperglycemic property which mimicking the insulin action. Thus, this study may provide significant implication in the discovery of the potential of these selected flavonoids as alternative anti-cancer, anti-inflammatory and anti-hyperglycemic drugs.